The impact of job performance planning in improving government institutional performance: An applied study on Palestinian ministries and governmental institutions - السقا , منذر صبحي عبدالله; حمدي , عبد الرحمن محمد عبدالله (Finance and Business Economies Review, 2023)
The study aimed to identify the impact of the application of job performance planning in improving the institutional performance of the Palestinian ministries and governmental institutions, through the analysis of the job performance planning stage. The comprehensive survey method was used in collecting and analyzing data, and to answer the study questions, the statistical package for social studies (SPSS) program was used. The most important results of the study are the existence of an effect of applying job performance planning in improving the Palestinian governmental institutional performance, and that the governmental institution sets specific and measurable goals at all administrative levels to a large extent, and there are clear and specific performance indicators to measure the results required to be achieved by employees in the ministry to a large extent.